2003
DOI: 10.3168/jds.s0022-0302(03)73629-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Milking Frequency Act Differently on Goat Mammary Gland in Late Lactation

Abstract: In ruminants, milk yield can be affected by treatment with growth hormone (rbGH) and/or changes in frequency of milking. Frequent milkings encourage the maintenance of lactation, whereas infrequent milkings result in mammary involution. Our objective was to evaluate the influence of rbGH treatment and milking frequency on mammary gland morphology and milk composition. After adaptation to twice-daily milkings, six Saanen goats in late lactation were milked once daily from one udder-half and thrice-daily from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 44 publications
5
47
1
5
Order By: Relevance
“…This suggests that apoptosis is not involved in the decrease in milk yield observed during ODM in goats. A previous study reported similar apoptotic rates in mammary tissue after 3 weeks of unilateral ODM in goats (Boutinaud et al, 2003). An increase in cell death in mammary tissue was reported after 4 weeks of unilateral ODM in goats (Li et al, 1999).…”
Section: Discussionsupporting
confidence: 58%
“…This suggests that apoptosis is not involved in the decrease in milk yield observed during ODM in goats. A previous study reported similar apoptotic rates in mammary tissue after 3 weeks of unilateral ODM in goats (Boutinaud et al, 2003). An increase in cell death in mammary tissue was reported after 4 weeks of unilateral ODM in goats (Li et al, 1999).…”
Section: Discussionsupporting
confidence: 58%
“…Boutinaud et al (2008) also observed an increase in Bax mRNA levels during ODM, with no significant change to the Bax/ Bcl-2 ratio in bovine milk MEC. In addition, ODM reduced the number of epithelial cells in the goat mammary gland (Boutinaud et al, 2003). Li et al (1999) had previously demonstrated an increase in the apoptosis rate in goat udders milked once daily for 3 weeks.…”
Section: Discussionmentioning
confidence: 93%
“…After three weeks of once-daily milking, the enzymatic activity of galactosyltransferase was reduced by 33% [30,31]. Two studies showed that a reduction in milking frequency had no effect on the level of α-lactalbumin gene expression [32,33]. Reduction in milking frequency also reduced the activity of the other major enzymes involved in mammary metabolism (acetyl co-enzyme A carboxylase, fatty acid synthetase) [31].…”
Section: Metabolic and Secretion Activitiesmentioning
confidence: 99%
“…cell death) of some mammary cells [34]. In the goat, Boutinaud et al [33] observed smaller alveolar diameters and lower numbers of mammary epithelial cells when once-daily milking was compared with milking three times a day.…”
Section: Metabolic and Secretion Activitiesmentioning
confidence: 99%